Foraging behaviour of wild Tufted Duck Aythya fuligula in winter - Sutherland, Ian T (Wildfowl, 2013)
The Tufted Duck Aythya fuligula is invariably an underwater feeder which exploits the benthos. Field observations made in the early 20th century found that Tufted Duck foraging in the wild had a dive to surface time ratio of approximately 2 : 1. More recent studies of captive Tufted Duck found that the dive to surface time ratio was about 1 : 1. This study re-examined the feeding behaviour of wild Tufted Duck wintering in the UK. Mean water temperature at the benthos was 6.2°C (s.d. ± 1.6°C) over the study period. The mean dive times of 23.4 s (± 2.5 s) for males and 22.2 s (± 1.6 s) for females were significantly greater than the mean between-dive surface times of 10.7 s (± 1.6 s) and 10.4 s (± 1.6 s) for males and females, respectively. The corresponding mean dive to surface time ratios were 2.3 : 1 (± 0.3) for males and 2.2 : 1 (± 0.3) for females. Both measures were significantly greater than the mean dive to surface time ratio of 1.1 : 1 (± 0.2) reported for freely foraging captive Tufted Duck in diving physiology studies.